Rigid versus non-rigid fixation for bilateral angle of mandible fractures: A 10 year perspective - Priyanka Raidoo; Timothy Manzie; Nathan Vujcich; Mustafa Mian; Alexander M. Bobinskas (Elsevier, 2022)
Background: Bilateral mandibular angle fractures are an uncommon occurrence. Optimal management of bilateral angle fractures is controversial and owing to the rarity of the presentation, limited evidence regarding fixation strategies exists. Methods: A retrospective chart review of patients treated at three tertiary hospitals in Western Australia between January 2008 and June 2018 was performed. Patient demographics, injury mechanism, fixation type and the use of intermaxillary fixation were recorded. Rigid fixation (increased plate thickness (>1mm), additional screws/plate length/additional plates) was compared against the complication rates between non-rigid fixation (Champy's load-sharing/mini-plate fixation principles). Primary end-points were complications requiring a return to theatre during the follow-up period. Results: During the study period, 2458 patients were managed with open reduction internal fixation. Fifty-eight bilateral angle of mandible fractures were identified, representing 2.4% overall. Nine patients had a complication during follow-up with 8 requiring a return to theatre for treatment. Statistical analysis demonstrated no increase in complication in either group. Conclusions: This study represents the largest review of patients with bilateral mandibular angle fractures. Given no increase in complication rates, it is suggested that the surgeons preference, incorporating fracture and patient factors be considered in determining the need for either rigid or non-rigid fixation for this particular fracture pattern.